UTILIZATION OF CASSAVA SKIN WASTE (Manihot utilissima) IN AFFECTING FE LEVELS IN WATER - Indah Pratiwi; Yusriani Sapta Dewi (Lembaga Penelitian, Publikasi, & Pengabdian kepada Masyarakat, Universitas Satya Negara Indonesia (LP3M-USNI), 2023)
This research is purposed to determine adsorbtion of activated carbon which is made from cassava peel to reduce heavy metals such as ion Fe in the water. The process is consist two main stages which is carbonisation and activation. The carbonization process was carried on different temperature such as 300, 400, 500, 550, 600 ˚C. Then a resulted 5 samples was soaked in 30% NaOH liquid for 1 hours. As the result the lowest water degree is 3,63% which is furnaced by 500˚C. Testing activated carbon absorption to heavy metals such as ion Fe using atomic adsorption spectrofotometric (AAS). The result showed that the most optimum adsorption is activated carbon that furnaced by 600 ˚C with value Effectiviy 51,97%